Respuesta :

Given:

The terms are [tex]-3a^2b^2,-\dfrac{5}{2}a^2b^2,4a^2b^2,\dfrac{2}{3}a^2b^2[/tex].

To find:

The sum of given terms.

Solution:

Sum of given terms is

[tex]-3a^2b^2+(-\dfrac{5}{2}a^2b^2)+4a^2b^2+\dfrac{2}{3}a^2b^2[/tex]

[tex]=-3a^2b^2-\dfrac{5}{2}a^2b^2+4a^2b^2+\dfrac{2}{3}a^2b^2[/tex]

Taking out common factors, we get

[tex]=\left(-3-\dfrac{5}{2}+4+\dfrac{2}{3}\right)a^2b^2[/tex]

[tex]=\left(\dfrac{-18-15+24+4}{6}\right)a^2b^2[/tex]

[tex]=\left(\dfrac{-5}{6}\right)a^2b^2[/tex]

[tex]=\dfrac{-5}{6}a^2b^2[/tex]

Therefore, the sum of given terms is [tex]\dfrac{-5}{6}a^2b^2[/tex].